Renewable energy, water, and environmental degradation: A global panel data approach - Muhammad Tariq Majeed; Tania Luni (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Climate change and changing climatic patterns are posing a threat to the sustainability of life on earth. Climate change is attributed to the accumulation of greenhouse gas emissions (GHG)in the atmosphere representing environmental degradation. This study explores the links of renewable energy, water withdrawal, andeconomic growth with environmental degradation and provides empirical evidence using the panel data of 166 countries over the period 1990-2017. The study used panel data techniques and reported the results obtained from Pooled OLS, Random Effects, Fixed Effects estimations and 2 Stage Least Square(2SLS). The results support the role of renewable energy in environmental mitigation whereas water withdrawal contributes to emissions. Furthermore, results supportthe existence of the EnvironmentalKuznets Curve (EKC). Empirical evidence also suggests the positive role of solar, wind, geothermal and hydroelectricity in environmental improvement. The sensitivity analysis also confirms the robustness of empirical findings. The sensitivity analysis also indicates the validity of N-shaped EKC. The study provides useful insights into the role played by renewable energy in environmental mitigation and water withdrawal in increasing emissions which help to promote the consumption and production of renewable energy and increase its share in the energy mix for environmental mitigation.
Keywords: 330; renewable energy consumption; water withdrawal; environmental degradation; carbon dioxide; urbanization